1985
DOI: 10.1128/aac.27.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new cephalosporin, BMY 28142, with other broad-spectrum beta-lactam antibiotics

Abstract: Bacteria. The 853 isolates of gram-negative species and 296 isolates of gramn-positive species were predominantly of recent clinical origin from numerous sources of broad geographical distribution. The isolates were stored as described previously (2, 4). The 3-lactamase-producing strains used to generate the data in Table 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
86
0
7

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(95 citation statements)
references
References 4 publications
2
86
0
7
Order By: Relevance
“…In vitro studies performed prior to the commercial availability of cefepime showed that the MIC 90 ranged from 0.06 to 0.5 g/ml (12,25,26). In contrast, an assessment of isolates from North American intensive care units in 2003 showed that the MIC 90 was 2 g/ml, with MICs of some isolates as high as Ͼ16 g/ml (20).…”
mentioning
confidence: 99%
“…In vitro studies performed prior to the commercial availability of cefepime showed that the MIC 90 ranged from 0.06 to 0.5 g/ml (12,25,26). In contrast, an assessment of isolates from North American intensive care units in 2003 showed that the MIC 90 was 2 g/ml, with MICs of some isolates as high as Ͼ16 g/ml (20).…”
mentioning
confidence: 99%
“…Similarly, the pharmacokinetic parameters of amikacin following the concurrent administration of cefepime and following the discontinuation of the cefepime therapy were not significantly altered. Cefepime and amikacin can be coadministered to patients with normal renal function by using the standard recommended dosing regimens.Cefepime (BMY-28142) is a new parenteral cephalosporin with significant potential advantages over other new cephalosporins and nontraditional ,3-lactam antibiotics with respect to its antimicrobial spectrum of activity (12,15). In addition, cefepime appears to have a low affinity for chromosomally derived P-lactamases (23).…”
mentioning
confidence: 99%
“…Cefepime (BMY-28142) is a new parenteral cephalosporin with significant potential advantages over other new cephalosporins and nontraditional ,3-lactam antibiotics with respect to its antimicrobial spectrum of activity (12,15). In addition, cefepime appears to have a low affinity for chromosomally derived P-lactamases (23).…”
mentioning
confidence: 99%
“…Escherichia coli CSase- (8) (Cephalothin-sensitive) E. coli CSase+ (9) (Cephalothin-resistant) Klebsiella pneumoniae (10) Proteus mirabilis (10) P. vulgaris (10) Providencia rettgeri (10) Morganella morganii (10) Enterobacter cloacae (7) Serratia marcescens (9) Pseudomonas aeruginosa Enterobacteriaceae were also highly susceptible to BMY-28142, and the MIC values of BMY-28142 against Klebsiella pneumoniae, Providencia rettgeri, Morganella morganii and Enterobacter cloacae were below 0.5 ug/ml. There were some ceftazidime-resistant strains among these bacteria, against which BMY-28142 showed higher activity than cefotaxime.…”
Section: Susceptibility Testsmentioning
confidence: 99%